Economic Development and Tourism at the Regional Level: A Literature Review Identifying Competitiveness Future Research Directions in Regional Tourism - Sianipar, Rosianna (Electronic Journal of Education, Social Economics and Technology, 2024)
This article examines the interplay between regional tourism, economic competitiveness, and regional development through an extensive review of existing literature. It explores theoretical frameworks that explain tourism’s contribution to economic growth and regional development, alongside their practical applications. Historically, regional development theories largely excluded tourism, as regional economics and location studies prioritized manufacturing and urban-centric development over services and rural areas. This oversight led to the emergence of tourism as an independent academic discipline, focused on tailored frameworks such as destination competitiveness and tourism marketing. The review identifies key determinants of regional tourism competitiveness, including governance quality, infrastructure, human capital, sustainability, and digital transformation, which collectively shape a region’s ability to attract and retain tourism-related economic benefits. It highlights the gaps in existing research, such as insufficient integration of regional competitiveness frameworks with localized socio-economic contexts and limited attention to climate resilience and stakeholder collaboration. This study concludes by proposing future research directions, including comparative studies across regions, interdisciplinary approaches to competitiveness, and the role of emerging technologies in shaping competitive and sustainable regional tourism ecosystems. These insights provide valuable guidance for academics, policymakers, and practitioners aiming to leverage tourism as a catalyst for sustainable regional economic growth.